Answer: y = 3
Step-by-step explanation: y−3=2(x+1)
We know that x=-1 and we want to solve for y
Put in x=-1
y-3 = 2(-1+1)
y-3 = 2(0)
y-3=0
Add 3 to each side
y-3+3 = 0+3
y =3
<h2>
Answer:</h2><h2><em><u>I</u></em><em><u> </u></em><em><u>think</u></em><em><u> </u></em><em><u>4</u></em><em><u>5</u></em><em><u> </u></em><em><u>is</u></em><em><u> </u></em><em><u>your</u></em><em><u> </u></em><em><u>answer</u></em><em><u> </u></em><em><u>buddy</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em><em><u>!</u></em><em><u>!</u></em></h2>
I decided to write out the answer in paint, you can see it as an attachment.